Do Reforms Aimed at Reducing Time to Graduation Work? Evidence from the Italian Higher Education System - Davide Malacrino; Samuel Nocito; Raffaele Saggio (CESifo GmbH, 2025)
This paper examines the impact of a reform aimed at expediting graduation times in Italian universities by reducing the number of exams students must pass to obtain the fixed number of credits required to graduate. Using event-study estimates that leverage the reform's staggered implementation, we find that this policy change led to an increase in on-time graduation rates but also resulted in a decreased probability of employment one-year post-graduation. However, this negative effect reverses into a positive one in the medium run. We show that these patterns are explained by students using the time gained from earlier graduation to pursue additional educational qualifications in the year following graduation.
Keywords: I23; I26; I28; J22; 330; higher education; policy evaluation; time to graduation; labor outcomes